Pengembangan Aplikasi SOS-MB Tentang Kebiasaan Efektif Untuk Penguatan Kemandirian Belajar Bagi Siswa SMP - Nofianti, Anja; Muslihati, Muslihati; Hambali, IM (Buletin Konseling Inovatif, 2025)
Learning independence is important for students today. The application of learning strategies must be considered with the advantages, disadvantages and uniqueness of student learning styles. Habit is a meeting between knowledge (knowledge), skills (skills), and desire (desire). To strengthen students' independent learning, counselors need to provide up-to-date services, one of which is the SOS-MB (SOS-Learning Independence) application. This application contains game material features, start playing and check independence. This research and development model uses the ADDIE model to develop the SOS-MB application and manual. From the results of product development, namely the SOS-MB application and guidebooks that have been tested for acceptability based on the criteria, usability, attractiveness and convenience aspects, it also turns out that the products developed can be accepted and used by school counselors. Also strengthened by the results of statistical tests that the application can be used for independent learning for junior high school students with the Wilcoxon test obtaining asymp sig.(2-tailed) 0.012 less than 0.05.